Prototype "Pengamanan Ganda" Pesan Rahasia Dengan Menggunakan Teknik Steganografi Metode LSB dan Kriptografi Metode Vigenere Cipher - Agung Wibowo (Jurnal Informatika, 2017)
Today information technology has growing into one of the world's most popular media. with the development of information technology is growing also acts misuse of information that is not right. then from development of information technology should also be coupled with the development of information security such as secret message. One way of securing data messages can be done with a combination of cryptography and steganography security techniques. The goal is to keep a message. the combination of cryptography and steganography believed to be a powerful way to protect messages sent and simultaneously avoid the message from suspicion.